Nonisotropic Self‐Assembly of Nanoparticles: From Compact Packing to Functional Aggregates. Issue 27 (8th May 2018) - Bouju, Xavier; Duguet, Étienne; Gauffre, Fabienne; Henry, Claude R.; Kahn, Myrtil L.; Mélinon, Patrice; Ravaine, Serge
Abstract: Quantum strongly correlated systems that exhibit interesting features in condensed matter physics often need an unachievable temperature or pressure range in classical materials. One solution is to introduce a scaling factor, namely, the lattice parameter. Synthetic heterostructures named superlattices or supracrystals are synthesized by the assembling of colloidal atoms. These include semiconductors, metals, and insulators for the exploitation of their unique properties. Most of them are currently limited to dense packing. However, some of desired properties need to adjust the colloidal atoms neighboring number. Here, the current state of research in nondense packing is summarized, discussing the benefits, outlining possible scenarios and methodologies, describing examples reported in the literature, briefly discussing the challenges, and offering preliminary conclusions. Penetrating such new and intriguing research fields demands a multidisciplinary approach accounting for the coupling of statistic physics, solid state and quantum physics, chemistry, computational science, and mathematics. Standard interactions between colloidal atoms and emerging fields, such as the use of Casimir forces, are reported. In particular, the focus is on the novelty of patchy colloidal atoms to meet this challenge. Abstract : Nondense packing of particles through self‐assembly is one of the main current challenges of nanotechnology. Penetrating this new and intriguing research field demands a multidisciplinary approach including statistical physics, solid‐state and quantum physics, chemistry, computational science, and mathematics. A comprehensive overview of the state‐of‐the‐art in directional self‐assembly is presented, with special attention to patchy particles.